Pengaruh penggunaan alokasi dana desa terhadap kesejahteraan masyarakat dengan akuntabilitas sebagai variabel moderasi - Ayu Aldira Sari; Laylan Syafina; Aqwa Naser Daulay (Keberlanjutan)
This study collects the perceptions of villagers in Perkebunan Pulahan Village, North Sumatra Province, to examine the influence of village fund allocation on community welfare. This research also uses accountability in village fund management as a moderating variable. Using a purposive sampling technique, the total sample in this study was 93 village communities. The data that has been collected is analyzed using the Ordinary Least Square (OLS) estimator. The results of this research show that village fund allocation has a positive effect on community welfare. This study also proved that accountability in village fund management can increase the influence of village fund allocation on community welfare. This accountability can trigger the realization of efficiency in developing a priority scale for using village funds to improve community welfare.